Identification and Characterization of Circulating Naïve CD4+ and CD8+ T Cells Recognizing Nickel - Bechara, Rami; Pollastro, Sabrina; Azoury, Marie Eliane; Szely, Natacha; Maillère, Bernard; de Vries, Niek; Pallardy, Marc (Frontiers in Immunology, 2019)
Allergic contact dermatitis caused by contact sensitizers is a T-cell-mediated inflammatory skin disease. The most prevalent contact allergens is nickel. Whereas memory T cells from nickel-allergic patients are well characterized, little is known concerning nickel-specific naïve T-cell repertoire. The purpose of this study was to identify and quantify naïve CD4+ and CD8+ T cells recognizing nickel in the general population. Using a T-cell priming in vitro assay based on autologous co-cultures between naïve T cells and dendritic cells loaded with nickel, we were able to detect a naïve CD4+ and CD8+ T-cell repertoire for nickel in 10/11 and 7/8 of the tested donors. We calculated a mean frequency of 0.49 nickel-specific naïve CD4+ T cells and 0.37 nickel-specific naïve CD8+ T cells per million of circulating naïve T cells. The activation of these specific T cells requires MHC molecules and alongside IFN-g production, some nickel-specific T-cells were able to produce granzyme-B. Interestingly, nickel-specific naïve CD4+ and CD8+ T cells showed a low rate of cross-reactivity with cobalt, another metallic hapten, frequently mixed with nickel in many alloys. Moreover, naïve CD4+ T cells showed a polyclonal TCRb composition and the presence of highly expanded clones with an enrichment and/or preferentially expansion of some TRBV genes that was donor and T-cell specific. Our results contribute to a better understanding of the mechanism of immunization to nickel and propose the T-cell priming assay as a useful tool to identify antigen-specific naïve T cells.